Causative role for defective expression of mitochondria‐eating protein in accumulation of mitochondria in thyroid oncocytic cell tumors. Issue 8 (30th June 2020) - Mussazhanova, Zhanna; Shimamura, Mika; Kurashige, Tomomi; Ito, Masahiro; Nakashima, Masahiro; Nagayama, Yuji
Abstract: Oncocytic cell tumor of the thyroid is composed of large polygonal cells with eosinophilic cytoplasm that is rich in mitochondria. These tumors frequently have the mutations in mitochondrial DNA encoding the mitochondrial electron transport system complex I. However, the mechanism for accumulation of abnormal mitochondria is unknown. A noncanonical mitophagy system has recently been identified, and mitochondria‐eating protein (MIEAP) plays a key role in this system. We therefore hypothesized that accumulation of abnormal mitochondria could be attributed to defective MIEAP expression in these tumors. We first show that MIEAP was expressed in all the conventional thyroid follicular adenomas (FAs)/adenomatous goiters (AGs) but not in oncocytic FAs/AGs; its expression was defective not only in oncocytic thyroid cancers but also in the majority of conventional thyroid cancers. Expression of MIEAP was not correlated with methylation status of the 5′‐UTR of the gene. Our functional analysis showed that exogenously induced MIEAP, but not PARK2, reduced the amounts of abnormal mitochondria, as indicated by decreased reactive oxygen species levels, mitochondrial DNA / nuclear DNA ratios, and cytoplasmic acidification. Therefore, together with previous studies showing that impaired mitochondrial function triggers compensatory mitochondrial biogenesis that causes an increase in the amounts of mitochondria, we conclude that, in oncocytic cell tumors of the thyroid, increased abnormal mitochondria cannot be efficiently eliminated because of a loss of MIEAP expression, ie impaired MIEAP‐mediated noncanonical mitophagy. Abstract : In this study, we sought to clarify the mechanisms for accumulation of abnormal mitochondria in oncocytic tumor of the thyroid and found a lack of expression of mitochondria‐eating protein (MIEAP), a molecule critical for non‐canonical mitophagy, in these tumors, and that exogenous expression of MIEAP accelerated mitochondrial turnover in oncocytic tumor cell line XTC.UC1. These data indicate that defective MIEAP expression causes accumulation of abnormal mitochondria in these tumors.